The arrival - Tan, Shaun (New York : A.A. Levine, 2007)
In this wordless graphic novel, a man leaves his homeland and sets off for a new country, where he must build a new life for himself and his family.
Added t.p. in unknown script.
A Junior Library Guild selection.
Keywords: Emigration and immigration -- Juvenile fiction; Immigrants -- Juvenile fiction; Stories without words; Comic books, strips, etc; Graphic novels; Children's Book of the Year Awards